2018
DOI: 10.1136/archdischild-2017-314560
|View full text |Cite
|
Sign up to set email alerts
|

Development of a gastroschisis core outcome set

Abstract: Objective Outcome reporting heterogeneity impedes identification of gold standard treatments for children born with gastroschisis. Use of core outcome sets (COSs) in research reduces outcome reporting heterogeneity and ensures that studies are relevant to patients. The aim of this study was to develop a gastroschisis COS. Design and setting Systematic reviews and stakeholder nomination were used to identify candidate outcomes that were subsequently prioritised by key stakeholders in a three-phase online Delphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 15 publications
1
46
0
Order By: Relevance
“…A Delphi process is a well established method for achieving consensus from multiple groups of stakeholders, 10 and has been used in health care for many purposes, including development of core outcome sets and identification of measures for monitoring quality of care. [11][12][13][14][15] Broadly, a Delphi process involves asking respondents to complete sequential questionnaires with group opinion relayed to individual participants between completion of the questionnaires. Children with PIMS-TS require the expertise of clinicians who specialise in immunology, infectious diseases, respiratory medicine, rheumatology, cardiology, intensive care, general paediatrics, haematology, and, in some cases, surgery, radiology, and neurology.…”
Section: Introductionmentioning
confidence: 99%
“…A Delphi process is a well established method for achieving consensus from multiple groups of stakeholders, 10 and has been used in health care for many purposes, including development of core outcome sets and identification of measures for monitoring quality of care. [11][12][13][14][15] Broadly, a Delphi process involves asking respondents to complete sequential questionnaires with group opinion relayed to individual participants between completion of the questionnaires. Children with PIMS-TS require the expertise of clinicians who specialise in immunology, infectious diseases, respiratory medicine, rheumatology, cardiology, intensive care, general paediatrics, haematology, and, in some cases, surgery, radiology, and neurology.…”
Section: Introductionmentioning
confidence: 99%
“…Of seven previously identified protocols, four had published a COS development study. (17)(18)(19)(20) Overall publications had increased in all areas of women's, newborn and neonatal health (figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The variation in outcome reporting was considerable: for example, a review of intrauterine growth restriction trials identified 238 outcomes and a review of bladder pain syndrome trials identified only five. (46,58) Published core outcome sets Twenty completed COS development studies were identified (table S6) (17)(18)(19)(20)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99) including: 13 (65%) in pregnancy and childbirth, 3 (15%) in newborn and neonatal health, 2 (10%) in benign gynaecology and subfertility and 2 (10%) in oncology. Sixteen studies (80%) were developed in an international context.…”
Section: Systematic Reviews Characterizing the Inconsistency In Outcomentioning
confidence: 99%
“…This contained maternal and neonatal outcomes, but the scope was limited to antenatal interventions. A number of core outcome sets have been developed in women’s health 36 ; in the newborn period these exist only for gastroschisis 46 and Hirschsprung’s disease, 47 with work under way for neonatal abstinence syndrome. 48 In rheumatology widespread adoption has led to full reporting of the rheumatoid arthritis core outcome set in 80% of relevant trials.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Starting in 2020 we will define measures and time points following OMERACT (Outcome Measures in Rheumatology) 2.0 methodology, 53 in collaboration with other international efforts. 54 55 Other core outcome sets have also been developed or are in development in the field of neonatology 46 48 ; it is important that overlapping core outcome sets are harmonised to avoid the multitude of incomparable outcomes being replaced by multiple incompatible core outcome sets. The aim is that future research will report the core outcome set alongside trial-specific outcomes; trial-specific outcomes will address a particular research question and core outcomes will provide data for meta-analyses, particularly for prospectively planned meta-analyses.…”
Section: Discussionmentioning
confidence: 99%